DOES FINANCIAL PLAN IMPACT INVESTMENT DECISIONS? - Chaurasia, Pratibha; Vijay, Priyanka (International Journal of Research -GRANTHAALAYAH, 2017)
Discipline is the bridge between goals and accomplishments and good financial habits bring discipline in financial decision making and have profound impact on the investment choices. This study proposes to study core financial habit of making financial plan adopted by individual investors while doing their investment planning and its impact on the investment preferences and objectives. In this study, survey approach has been adopted using a structured questionnaire with 559 sample size. The study has been taken within the geographical area of Indore and Ujjain district in Madhya Pradesh State of Central India. It has been found from the analysis that financial habits of investors play a crucial role in their investment preferences and objectives. Analysis has been done using Mann Whitney U test. The results of the research paper would contribute in developing understanding of the impact of financial habits on investment behavior and choices and thus serves an important insight to investors, financial planning professionals and other stakeholders linked to financial planning.